Biotransformation of dioxins by assembling RW1 upper pathway gene cassettes in Escherichia coli - THAMER Y. MUTTER; GERBEN J. ZYLSTRA; XING HUANG (Society for Indonesian Biodiversity, 2023)
Abstract. Mutter TY, Zylstra GJ, Huang X. 2023. Biotransformation of dioxins by assembling RW1 upper pathway gene cassettes in Escherichia coli. Biodiversitas 24: 3648-3656. Rhizorhabdus wittichii RW1 (formerly known as Sphingomonas) is one of the few bacterial strains known to grow and metabolize dibenzofuran and dibenzo-p-dioxin as a carbon source. The rare ability of strain RW1 to transform both substrates suggests the involvement of unidentified genes. Its genome sequence showed that RW1 has an extreme redundancy of ring cleavage dioxygenases and hydrolases. RW1 genes were assembled on an expression vector to provide additional experimental evidence that both substrates are metabolized in RW1 by two different sets of hydrolases. Three different combinations of the ring cleavage dioxygenase gene (dbfB2) with three hydrolases (dxnB1, dxnB2, and dxnB3) were cloned on an expression vector (pET30a) in Escherichia coli BL21 (DE3), and the enzymes' roles were tested against DD and DF transformation. The results of the heterologous expression in E. coli showed that DbfB2 can transform both intermediates 2,2?,3-trihydroxybiphenyl (THD) and 2,2?,3-trihydroxybiphenyl ether (THDE) from DF and DD, respectively. The two hydrolases DxnB1 and DxnB2 are involved only in transforming the DF intermediate 2-hydroxy-6-oxo-6-(2-hydroxyphenyl)-hexa-2,4-dienoate (2OH-HOPDA) into salicylate. The newly identified hydrolase DxnB3 is involved only in transforming 2-hydroxy-6-oxo-6-(2-hydroxyphenoxy)-hexa-2,4-dienoate (2OH-O-HOPDA) into catechol in the DD pathway. The study clarifies and answers the question regarding the rare ability of other organisms that can degrade dibenzofuran but can’t degrade dibenzo-p-dioxin. The results showed that the hydrolases involved in DD degradation differ from those involved in DF degradation, as previously known that the same hydrolases are involved in the two pathways. All genes are assembled on one cassette for the first time, which has never been done previously.